INFLUENCES ON SOUVENIR BUYING INTENTIONS OF TOURISTS IN CRAFTS-RICH REGIONS - DEY, BANASREE (ASEAN Journal on Hospitality and Tourism, 2012)
Souvenirs provide a tangible evidence of the travel experience. Souvenir purchase has been considered as an important component of tourism shopping. This has implications for tourism marketers and local artisans of regions that have a significant repertoire of traditional handicrafts/handloom products and may be regarded as craft-rich regions. The primary purpose of this study is to examine the souvenir purchase intentions of tourist segments to one such region - Northeast India. It aims to assess whether the intention to purchase souvenirs differs according to the type of tourist. The influence of travel motivations, activity preferences, demographics and certain trip-related factors on souvenir purchase intentions is examined. Using factor-cluster segmentation approach, three motive-based segments and three activity-based segments have been derived. Findings indicate that these segments differ with respect to purchase of souvenir. However, among the demographic and trip-related factors examined, only age and travel frequency are found to have an influence on intentions to purchase souvenirs. Tourism retailers of the region could benefit from such knowledge and may develop travel packages/ tour itineraries to cater to the interests of specific segments of tourists.